2005
DOI: 10.1016/j.virol.2005.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infection with mouse adenovirus type 1

Abstract: Studies of the pathogenesis of adenovirus respiratory disease are limited by the strict species-specificity of the adenoviruses. Following intranasal inoculation of adult C57BL/6 mice with mouse adenovirus type 1 (MAV-1), we detected MAV-1 early region 3 (E3) and hexon gene expression in the lungs at 7 days post-infection (dpi). We detected MAV-1 E3 protein in the respiratory epithelium at 7 dpi. We did not detect viral mRNA or protein at 14 dpi, but MAV-1 DNA was detected by PCR at 21 dpi. Chemokine transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 91 publications
(110 reference statements)
8
48
0
Order By: Relevance
“…Consistent with our previous reports (40,41), patchy areas of cellular inflammation developed in the lungs of infected adult mice beginning by 7 dpi (Fig. 4A, right columns).…”
Section: Mav-1 Viral Loads In Lungs Of Neonates and Adultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous reports (40,41), patchy areas of cellular inflammation developed in the lungs of infected adult mice beginning by 7 dpi (Fig. 4A, right columns).…”
Section: Mav-1 Viral Loads In Lungs Of Neonates and Adultssupporting
confidence: 92%
“…Acute MAV-1 infection induces the expression of multiple cytokines and chemokines in the lungs of adult mice (40,41). To determine whether virus-induced cytokine production differs between neonates and adults, we measured protein and mRNA levels of representative Th1 (IFN-␥) and Th2 (IL-4) cytokines along with those of chemokines (CCL5 and CXCL1) that are typically induced in the lung by acute MAV-1 respiratory infection.…”
Section: Mav-1 Viral Loads In Lungs Of Neonates and Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAV-1 causes a widely disseminated infection in mice, targeting endothelial cells and cells of the monocyte lineage (13,21,28,31) and, after intranasal inoculation, respiratory epithelial cells (61). Defining the factors involved in the tropism of MAV-1 will include identifying the receptors used by the virus.…”
Section: Discussionmentioning
confidence: 99%
“…mouse adenovirus 1 (MAV-1) infection of C57BL/6 and BALB/c mice as a model to study the pathogenesis of adenovirus respiratory infection (19). One previous report demonstrated that intraperitoneal (i.p.)…”
mentioning
confidence: 99%